A Review on Performance and Emission of CI Engine using Exhaust gas recirculation (EGR). (November 2019) - Dubey, Aseem; Ahmad Ansari, Naushad; Kumar, Girish; Arora, Akhilesh; Sharma, Abhishek
Abstract: The diesel engine has the advantage over gasoline engine due to its low fuel consumption, higher combustion efficiency, durability and low hydrocarbons (HC), particulate, carbon dioxide (CO2 ), carbon monoxide (CO) and NOX emission as a major source. Due to abovesaid problems, diesel is now blended with Biofuels and play a significant role to meet its energy and environmental challenges. Exhaust gas recirculation (EGR) is an eco-friendly alternativeto lower NOX and particulates emission. The use of EGR in compression ignition engines, lowers the concentration of oxygen mixture and flame temperature. However, it has been observed that advantages of EGR is fuel specific. In present paper a performance review of compression ignitionengine using EGR with blended fuelshas been carried out. The effect on break power, break specific fuel consumption, thermal efficiency has been reported. Further aspects of response surface methodology on optimization of NOx emission, smoke opacity and BSFChasbeen carriedout using blended fuel, EGR rate, injection timing etc.